DESIGN AND SIMULATION OF PHOTONIC CRYSTAL FIBERS TO EVALUATE DISPERSION AND CONFINEMENT LOSS FOR WAVELENGTH DIVISION MULTIPLEXING SYSTEMS - Khalid, M.; Arshad, I.; Zafarullah, M. (The Nucleus, 2014)
Photonic Crystal Fiber (PCF) is the innovative and vital advancement in the field of optical communication. Research is being carried out in this field to study the transmission properties of PCF and how these properties can be improved to get the most optimum design. In this paper, two different categories of PCF are used (i) single solid-core PCF and (ii) multi solid-core PCF. We evaluated the confinement loss and dispersion properties for different designs of PCF to find an appropriate design for effective propagation of light in wavelength division multiplexing (WDM) systems. For WDM systems, both the confinement loss and dispersion of the fiber should be minimized for effective propagation of light. We made different designs of PCF and compared them to achieve the best possible design. The wavelength range for WDM systems is from 1300nm to 1500nm. We studied the confinement loss and dispersion for this range of wavelengths.